Dimensions Of Contemplative Tendency Of Mikha'il Na'ima In His Work “Najwal Ghuroub” Soliloquy Of The Sundown - Hilal, Reem (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research tackles contemplative tendency, which was evident in Mikha'il Na'ima’s work “Najwal Ghuroub” Soliloquy of the Sundown , and became more intense throughout his pages , not exceeding a hundred and some scores of pages, covering the elements the author witnessed throughout his life ,which drove him to ponder and think over, starting with the Creator, maker of the universe, and ending therewith, and between this beginning and end, passing by the wonders, which Na'ima found around him , then going up towards that which he sets eyes on through the unending space horizons ; and that which he doesn’t, then coming down with his contemplations , returning to the earth with all that it contains ; added to that is his reflecting on the individual ego ,to which he attached all those elements, comparing them in each contemplative stop, to find out their disparity both in volume and worth , which each of which maintaining its wonders. يتناول هذا البحث النزعة التأمُّليَّة التي تجلَّت واضحةً في مؤلَّف ميخائيل نُعَيمة " نجوى الغروب " ، وتكثَّفَت عبرَ صفحاته التي لم تتجاوز بضعاً قليلاً من عشرات الصفحات بعد المئة، شاملةً ما شهده المؤلِّف عبرَ حياته من عناصر، قد حملَتْه على التبصُّر والتفكُّر ، بدءاً من الخالق مبدع الكون ، وانتهاءً به ، مروراً ما بين البداية والنهاية هاتَين بالعجائب التي ألفاها نُعَيمة تحيط به ، ثم ارتقاءً نحو ما يبصر وما لا يبصر عبرَ آفاق الفضاء اللامتناهية ، ثم هبوطاً بتأمُّلاته عائداً إلى كوكب الأرض بمن فيه وما فيه . يُضاف إلى ذلك وقوفه متأمِّلاً عند الذات الفرديّة ، التي أرفَقَها بكلٍّ من تلك العناصر ، مقارِناً في كلّ محطَّة تأمُّليَّة ما بينهما ، لكي يتبيّن له تفاوتهما حجماً وقدراً ، مع احتفاظ كلٍّ منهما بعجائبه .